Outcomes of Patients Referred for Arteriovenous Fistula Construction: A Systematic Review - Andrew Stanton Kucey; Anish Engineer; Shawn Stefan Albers (University Library System, University of Pittsburgh, 2019)
Chronic Kidney Disease (CKD) affects 10-16% of the US population and its incidence is rising due to increasing prevalence of associated risk factors. Renal replacement therapy is required to treat late stage CKD and hemodialysis is the preferred modality for many patients. Vascular access is required for hemodialysis and arteriovenous fistulas (AVF) are currently the gold standard. This review intended to collate current knowledge on AVF outcomes regarding both the patient and fistula. Scopus and Medline were utilized to identify relevant literature. Inclusion and exclusion criteria were applied to narrow search results. Among CKD patients, 33.5-77.4% require a central venous catheter (CVC) before dialysis through a fistula. Many patients (33-51%) use a CVC regardless of AVF creation due to fistula immaturity or failure. There are large variations in AVF creation policies internationally; 16% of American hemodialysis patients use a fistula compared to 72% of German patients. Primary patency and primary AVFs' failure ranges from 60-70% and 20-26%, respectively. AVFs reduce morbidity and mortality in CKD. At present, too many patients are receiving hemodialysis through a CVC. Inadequate referral times for AVF creation can lead to fistula immaturity or failure in the intervention. Many countries are lagging behind recommended AVF creation rates published by the Kidney Disease Outcomes Quality Initiative. There is a paucity of literature concerning when a patient should be referred for AVF creation. It is paramount to have better predictive outcome measures and more clarity as to when patients will benefit from an AVF.